The Effect of Cost of Goods Sold (COGS) and Profit Contribution on Sales Volume - Aisy, Nabilah Rihadatul; Suhartono; Hakim, Lukman; Yanti, Vera Agustina; Kuspriyono, Taat; Abdurrachman (Nomico, 2025)
In general, profit is a goal that must be achieved by the company to realize profits for the company. Where sources (Input), such as raw materials and labor are processed to produce goods or services (Output) for customers. Companies need to have products that can be sold to the general public, these products are non-physical products, raw materials or finished products that can be consumed. Researchers used a quantitative descriptive approach in this research to determine the influence of cost of goods sold and profit contribution on sales volume in manufacturing companies listed on the IDX. Researchers will explain how cost of goods sold and contribution profit affect sales volume. The research results indicate that Cost of Goods Sold (COGS) and Contribution Profit have a significant influence on the Sales Volume of manufacturing companies in Indonesia during the 2020-2022 period.